Election Dispute Resolution and Justice as Fairness: A Study of Regional Head Elections in Indonesia - Ervan Kus Indarto; Arya Wanda Wirayuda; Oni Dwi Arianto; Rima Firdaus; Henry Ufomba (Jurnal Mengkaji Indonesia, 2023)
Abstract: The concept of justice is still relevant for debate, involving two political and legal perspectives. However, the two met in the context of resolving election disputes. Namely the election justice mechanism to resolve all forms of election disputes. This study will focus on resolving election result disputes, the 2020 Regional Head Election Results Dispute. John Rawls is a philosopher and political theorist who strongly influenced the tradition of justice theory. The concept of justice is offered from criticism of utilitarianism and intuitionism. Justice as fairness is a concept of justice that is procedurally fair but also justice that benefits as well as opportunities that are just (equal). Purpose: This article aims to elaborate Regional Head Election Results Dispute from Rawls’ justice as fairness approach to resolve election disputes. Design/Methodology/Approach: The research method used is qualitative research. Using a descriptive approach and literature study as data collection techniques.  Findings: There is still a serious debate about achieving the concept of justice between substantive and procedural justice in electoral studies regarding the equitable settlement of election result disputes. A just Regional Head Election Results Dispute indicates the degree of democracy in implementing direct, general, free, confidential, and honest, fair elections (LUBER JURDIL). Constitutional democracy is a meeting point between Rawls' democratic tradition and Plato's nomocracy. Originality/value: Many articles on Regional Head Election Results Dispute philosophically explain Rawls’ justice as a fairness concept. However, this article explores the relationship between Regional Head Election Results Dispute phenomenon through Rawls’ philosophical concepts.